A New Surgical Approach for Tessier No. 4 Facial Cleft Reconstruction: Lip-Rescue Flap. Issue 8 (November 2016) - Horoz, Ugur; Kuroki, Tomoaki; Sato, Nabuhiro; Tosa, Yasuyoshi; Ozakpinar, Hulda Rifat; Tellioglu, Ali Teoman; Yoshimoto, Shinya
Abstract : Abstract: Craniofacial clefts are rare, severe challenges for surgeons about which there is limited literature. Tessier Number 4 (No. 4) clefts are one of the most complex craniofacial anomalies and present difficulties in surgical treatment. The most-common deformities associated with Tessier No. 4 clefts are displacements of the lower eyelids, medial canthus, and ala and decreased distance between the lower eyelids and lips. In surgery to correct these deformities, the greatest challenges are the design and the placement of the landmarks and incisions. Because of its relative rarity and wide range of severity, no definitive operative methods have been accepted for Tessier No. 4 facial cleft. The present study presents a new lip-rescue flap technique as an alternative approach for reconstructing Tessier No. 4 facial clefts.